Undergrads Set To Speak Their Minds - NEw Straits Times, (2008)
COURAGEOUS, dedicated and outspoken best describe the four undergraduates who will represent Malaysia at the Ninth Hitachi Young Leaders Initiative (9th HYLI) in Jakarta Indonesia in July.